Innovation credit: when can leaders oppose their group's norms? - Dominic Abrams (2008)
Two preliminary studies and 5 experiments examined judgments of leaders who challenge their group's norms. Participants viewed information about group members whose attitudes were normative or deviated in a pronormative or antinormative direction. The antinorm member was identified as (a) either a nonleader or an established leader (Study 1), (b) an ex-leader (Studies 2 and 5), or (c) a future leader (Studies 3, 4, and 5). Antinorm future leaders were judged more positively and were granted greater innovation credit (license to innovate and remuneration) relative to antinorm members, ex-leaders, and established leaders. Results are discussed in terms of the idea that leadership can accrue from prototypicality and can also confer the right to define prescriptive norms. However, innovation credit is only granted in the case of future leaders.